Pengaruh Penggunaan Media Pembelajaran Multimedia Interaktif Terhadap Pemahaman Materi Fiqih Siswa MTsN 1 Model Medan - Fadilla, Mutia; Sakinah, Nur; Andriani, Andriani; Setiawan, Hasrian Rudi (Jurnal Pendidikan Islam Indonesia, 2025)
This study aims to determine the effect of using interactive multimedia learning media on students’ understanding of fiqh material among eighth-grade students at MTsN 1 Medan. The background of this research is based on the low level of students’ learning interest and understanding of fiqh subjects, which is caused by the use of conventional teaching methods that are less engaging and monotonous. Therefore, innovation in learning media is needed to increase student involvement and understanding. The research method employed is a quantitative approach using a quasi-experimental design. The study involved two groups: an experimental group that was taught using interactive multimedia and a control group that was taught using conventional learning methods. Research instruments included achievement tests, questionnaires, and observation sheets to measure students’ understanding and responses to the learning process. The results of the instrument validity test showed that 17 out of 20 test items were valid, with a high level of reliability indicated by a Cronbach’s Alpha value of 0.930. Prerequisite tests, including normality, linearity, and heteroscedasticity tests, demonstrated that the data met the requirements for linear regression analysis. The regression analysis produced the equation Y = 17.002 + 0.604X, with a significance value of 0.001 < 0.05 and a calculated t-value greater than the t-table value, indicating that interactive multimedia learning media have a positive and significant effect on students’ understanding of fiqh material.